Nashville - Baskin, Richard (Winklerfilm, 2013)
Nashville interweaves the stories of 24 characters over 5 days during a political rally in the capital of country music.
FSK ab 12 Jahren
Bildformat 2.35:1 (16:9)
Orig.: USA 1975
Enth. Interview mit Robert Altman ; Audiokommentar mit Robert Altman (engl. ohne Untertitel)
Keywords: USA -- Präsident; Geschichte 1976; Country music -- Tennessee -- Nashville -- Drama; Feature films; Films for the hearing impaired; Präsidentenwahl; Countrymusic; Wahlkampf; Nashville (Tenn.) -- Drama; Nashville, Tenn.; Film; Video recordings for the hearing impaired